Extracellular vesicles from patients with Acute Coronary Syndrome impact on ischemia-reperfusion injury - D’Ascenzo, Fabrizio; Femminò, Saveria; Ravera, Francesco; Angelini, Filippo; Caccioppo, Andrea; Franchin, Luca; Grosso, Alberto; Comità, Stefano; Cavallari, Claudia; Penna, Claudia; De Ferrari, Gaetano Maria; Camussi, Giovanni; et al. (Pharmacological research, 2021)
The relevance of extracellular vesicles (EV) as mediators of cardiac damage or recovery upon Ischemia Reperfusion Injury (IRI) and Remote Ischemic PreConditioning (RIPC) is controversial. This study aimed to investigate whether serum-derived EV, recovered from patients with Acute Coronary Syndrome (ACS) and subjected to the RIPC or sham procedures, may be a suitable therapeutic approach to prevent IRI during Percutaneous-Coronary-Intervention (PCI). A double-blind, randomized, sham-controlled study (NCT02195726) has been extended, and EV were recovered from 30 patients who were randomly assigned (1:1) to undergo the RIPC- (EV-RIPC) or sham-procedures (EV-naive) before PCI. Patient-derived EV were analyzed by TEM, FACS and western blot. We found that troponin (TnT) was enriched in EV, compared to healthy subjects, regardless of diagnosis. EV-naive induced protection against IRI, both in-vitro and in the rat heart, unlike EV-RIPC. We noticed that EV-naive led to STAT-3 phosphorylation, while EV-RIPC to Erk-1/2 activation in the rat heart. Pre-treatment of the rat heart with specific STAT-3 and Erk-1/2 inhibitors led us to demonstrate that STAT-3 is crucial for EV-naive-mediated protection. In the same model, Erk-1/2 inhibition rescued STAT-3 activation and protection upon EV-RIPC treatment. 84 Human Cardiovascular Disease mRNAs were screened and DUSP6 mRNA was found enriched in patient-derived EV-naive. Indeed, DUSP6 silencing in EV-naive prevented STAT-3 phosphorylation and cardio-protection in the rat heart. This analysis of ACS-patients’ EV proved: (i) EV-naive cardio-protective activity and mechanism of action; (ii) the lack of EV-RIPC-mediated cardio-protection; (iii) the properness of the in-vitro assay to predict EV effectiveness in-vivo. [Display omitted]